Introduction to Christianity: A Case Method Approach - ., K.T.K (Journal of Dharma, 1980)
Alice E. and Robert A. Evans, Introduction to Christianity: A Case Method Approach, Atlanta: John Knox Press, 1980, pp. xi + 226, $ 6.95.